Analysis of Landscape Visual Aesthetic Potential in Ocean Dream Samudra Ancol Recreation Area, Jakarta with Visual Resources Assessment Procedure Method - Nisrina Fakhira; Titien Suryanti Rostian; Rini Fitri (Universitas Trisakti, 2022)
Recreation area The Ocean Dream Samudra Ancol, one of the largest aquatic mammal educational recreation areas in Jakarta, is called the largest Oceanarium located in the Taman Impian Jaya Ancol, Jakarta. It has various potentials both from natural and artificial resources in its visual landscape. The landscape arrangement in the Ocean Dream Samudra Ancol recreation area has not been used optimally. This study aims to analyze the visual aesthetic aspects of the landscape to find out the visual aesthetic quality in the Ocean Dream Samudra Ancol recreation area and at activity points that are often visited by visitors. Based on this, it is necessary to analyze the visual aesthetic potential of the landscape in the Ocean Dream Samudra Ancol recreation area through the Visual Resource Assessment Procedure (VRAP) as a method of determining the visual aesthetic value of the landscape by using a variable assessment table at each potential activity point (View Point) with Macro visa assessment approach. The final result of this research study is a value at the point of the activity area that has attractive visual aesthetic potential or not. So that it can be known what values and elements exist that must be maintained, modified, preserved or rehabilitated in the area.